Morfofunkcional'nye i psichofiziologiceskie osobennosti sportsmenov 19-22 let, zanimajuscichsja sportivnoj aerobikoj - Filippova, Ju. S.; Rubanovic, V. B.; Ajzman, R. I. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
This research contributes to the solution of the following questions. What are the somatotype, physical work capacity, muscular strength and flexibility of athletes? How the sports aerobics influences the cardio- respiratory system of girls? What dominating psycho physiological particularities do girls have in sports aerobics?